Optimization of Bread Baking Parameters in Conventional Oven - Gundu, Rajender; Datta, A K; Jayashree, G C (Journal of Agricultural Engineering, 2012)
Optimization of baking parameters in conventional oven was done for cup breads to hasten the bread baking process. The breads were baked at three different baking temperatures of 175 oC, 200 oC and 225 oC at 5 min interval in range of 5 min to 30 min at each temperature. The crumb moisture content, crust hardness and colour were determined and the operating parameters were optimized as: (1) 175 oC and 30 min, (2) 200 oC and 25 min and (3) 225 oC and 20 min.